Survey About Hand Pain: New York University College of Dentistry Students - Mea A. Weinberg; Stuart L. Segelnick; Enas Bsoul; Peter M. Loomer (Taylor & Francis Group, 2023)
ABSTRACTBackground The objective of this study was to determine the prevalence and associated risk factors for current hand musculoskeletal pain in dental students at a dental school.Methods 1,889 dental students and postgraduate residents were recruited from the clinics at New York University College of Dentistry to participate in a closed-ended survey on hand pain.Results The close-ended survey was completed by 373 dental students (20% response rate) of which 30.6% were D2, 30.6% D3, 27.2% D4, and 11.6% postgraduate. 235 (63.0%) reported musculoskeletal pain of the hand/wrist/fingers while a student at the school. The majority who reported pain responded that it lasted seconds (21.7%) or minutes (42.5%) in duration. However, 35.3% of those with pain described it as moderate or severe, of whom 26.0% reported visiting a physician for their symptoms. There was no overall statistically significant difference in hand/wrist/finger pain by year in dental school training.Conclusions Hand musculoskeletal pain may be common among dental students and residents and can be severe for some individuals. Future research should consider the contributions of dental school training on hand pain among students (potentially combined with other factors like mobile phone, tablet, and computer use), as well as implementation of preventive ergonomic training.